Soy protein and human nutrition : proceedings of the Keystone Conference on Soy Protein and Human Nutrition, held in Keystone, Colorado, May 22-25, 1978 - Wilcke, Harold Ludwig, 1906-; Hopkins, Daniel T.; Waggle, Doyle H. (Academic press manuscript reproduction., 1979)
ACKNOWLEDGEMENT; REFERENCES; DISCUSSION; CHAPTER 6. NUTRITIONAL QUALITY OF SOYBEAN PROTEIN ISOLATES: STUDIES IN CHILDREN OF PRESCHOOL AGE; EXPERIMENTAL DESIGN AND PROCEDURES; RESULTS; DISCUSSION; ACKNOWLEDGEMENTS; REFERENCES; CHAPTER 7. SOY PROTEIN IN ADULT HUMAN NUTRITION: A REVIEW WITH NEW DATA; INTRODUCTION; AVAILABLE DATA ON SOY PROTEIN QUALITY FOR ADULT HUMANS; MIT STUDIES OF SOY PROTEIN; EVALUATION OF SOY PROTEIN QUALITY; COMPARISON OF THE PROTEIN QUALITY OF SOY PRODUCTS AND BEEF; LONG-TERM TOLERANCE AND ACCEPTABILITY OF SOY PROTEIN PRODUCTS; SUMMARY; ACKNOWLEDGEMENTS; REFERENCES